Patterns of Indonesian Language Online Learning During Pandemic in Malang City - Tahmida, Nova Shufia; Widyartono, Didin (OKARA: Jurnal Bahasa dan Sastra, 2022)
System changes that occur quickly and suddenly during a pandemic change learning patterns. This can be seen in the pattern of learning including planning, implementation, and assessment. This present study aimed to find out the activities of Indonesian junior high school teachers throughout the city of Malang in online learning of the Indonesian language during the pandemic, which was elaborated in the form of percentages. This present study applied quantitative-descriptive research by using a survey method. Meanwhile, the data collection was performed by using a questionnaire with data analysis in the form of a percentage description. Afterward, the results showed that online learning based on the perspective of junior high school teachers in Malang city consisted of teachers’ activities at the planning step (determining of K13 guidelines and provisional curriculum in the preparation of lesson plans was 100%), action step (doing mixed learning 47.6%), and assessment step (determining the principle of assessment of special conditions by adjusting the conditions and needs of students as much as 86.7%). This study indicates that online learning in Malang Junior High School during the pandemic makes teachers find distinctive language learning patterns based on the patterns of learning.